A new and poorly known clearwing moth of the genus Bembecia Hübner, 1819 [“1816”] from the European part of Russia and northwestern Kazakhstan (Lepidoptera, Sesiidae) - Gorbunov, Oleg G. (Zootaxa, 2020)
A new species, Bembecia pallasi sp. nov. is described and illustrated from the European part of Russia and northwestern Kazakhstan. Data on its habitat, host plants and larval biology are presented and illustrated as well. B. sareptana (Bartel, 1912) is reviewed and its morphology, biology of preimaginals and habitat are described and illustrated.